Patient-related beliefs and adherence toward their medications among the adult hypertensive outpatients in Tanzania. (May 2017) - Jande, Mary; Katabalo, Deogratias M; Sravanam, Praveen; Marwa, Carol; Madlan, Bijal; Burger, Johanita; Godman, Brian; Oluka, Margaret; Massele, Amos; Mwita, Stanley
Aim: Hypertension is a leading global health problem requiring lifelong treatment. However, adherence to antihypertensive medicines is a problem, greater among developing countries. Consequently, there is a need to determine current adherence rates and their associations among developing countries to plan future initiatives.Materials & methods: Cross-sectional study among adult outpatients with essential hypertension in Tanzania. Predesigned questionnaires were used to gather information on adherence rates and patient-related beliefs. The main outcome measure was adherence.Results: A total of 180 participants were included, with females making up 65%. High-adherence rates were seen in 54% of the patients. Patients' belief about their medication and its necessity was higher in the high adherent group and concerns about their medicines and their necessity were higher in the low adherent group.Conclusion & recommendations: Adherence rates were low compared with a suggested level ≥80%. Educational initiatives are needed to address knowledge and concerns with hypertension to improve future outcomes.